Peningkatan Literasi Digital dan Etika Bermedia Sosial Bagi Santri Dayah Darul Muta'alimin - Jauharil Maknuni; Ishaq (BA: Jurnal Pengabdian kepada Masyarakat, 2024)
The rapid development of information technology has transformed the way people live, including how they communicate and interact socially. Social media has become one of the main platforms for individuals, including students at Islamic boarding schools (santri), to communicate and access information. However, not all social media users possess adequate digital literacy, making them vulnerable to the spread of misinformation (hoaxes) and negative behaviors. Therefore, improving digital literacy and understanding social media ethics is crucial, especially for santri in pesantren. The program "Enhancing Digital Literacy and Social Media Ethics for Santri at Dayah Darul Muta’alimin" aims to equip santri with the knowledge and skills needed to use digital technology wisely and responsibly. Through interactive lectures, group discussions, case studies, and practical content creation, this program successfully improved the santri’s understanding of the importance of digital literacy and ethics in social media. The evaluation showed significant improvements in the santri’s attitudes toward social media ethics, as well as their ability to create beneficial content in alignment with Islamic values. The outcomes of this program contribute positively to the development of santri who are digitally literate and responsible in using social media as a platform for da’wah and social interaction.